2017
DOI: 10.1126/scitranslmed.aaf5294
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of protease-activated receptor-4 (PAR4) provides robust antithrombotic activity with low bleeding

Abstract: Antiplatelet agents are proven efficacious treatments for cardiovascular and cerebrovascular diseases. However, the existing drugs are compromised by unwanted and sometimes life-threatening bleeding that limits drug usage or dosage. There is a substantial unmet medical need for an antiplatelet drug with strong efficacy and low bleeding risk. Thrombin is a potent platelet agonist that directly induces platelet activation via the G protein (heterotrimeric guanine nucleotide-binding protein)-coupled protease-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
155
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(164 citation statements)
references
References 59 publications
3
155
0
1
Order By: Relevance
“…BMS-986120 blocked human platelet activation in platelet-rich plasma stimulated by γ-thrombin or a PAR4 activation peptide with an IC 50 <10 nmol/L. 12 The most compelling findings in this study resulted from a direct comparison of BMS-986120 to clopidogrel in a nonhuman primate thrombosis model. BMS-986120 administered orally at 1 mg/kg decreased thrombus weight by 80% with limited bleeding risk.…”
Section: See Accompanying Article On Page 448mentioning
confidence: 75%
See 3 more Smart Citations
“…BMS-986120 blocked human platelet activation in platelet-rich plasma stimulated by γ-thrombin or a PAR4 activation peptide with an IC 50 <10 nmol/L. 12 The most compelling findings in this study resulted from a direct comparison of BMS-986120 to clopidogrel in a nonhuman primate thrombosis model. BMS-986120 administered orally at 1 mg/kg decreased thrombus weight by 80% with limited bleeding risk.…”
Section: See Accompanying Article On Page 448mentioning
confidence: 75%
“…In contrast, the dose of clopidogrel that achieved >80% reduction in thrombus weight (1 mg/kg) led to >8-fold increase in bleeding. 12 This comprehensive study showed BMS-986120 to be an effective PAR4 antagonist with a lower bleeding risk and a wider therapeutic window compared with clopidogrel.…”
Section: See Accompanying Article On Page 448mentioning
confidence: 92%
See 2 more Smart Citations
“…The recent preclinical study by Wong et al (5) details the development and preclinical evaluation of the first PAR4 antagonist to enter a clinical trial and represents a potentially important breakthrough in the treatment of arterial thrombosis. While further insights are still to be gained regarding the utility of PAR4 antagonism in clinical settings, this study has contributed an important reagent to help study this previously under-appreciated platelet activation mechanism, and has identified a potentially useful approach for the safe and effective prevention of arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%